2022
DOI: 10.3389/fnut.2022.816883
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Sarcopenia in Patients With Diffuse Large B-Cell Lymphoma Treated With R-CHOP: A Systematic Review and Meta-Analysis

Abstract: ObjectiveSeveral studies have reported conflicting results regarding the association between sarcopenia and outcomes in patients with diffuse large B-cell lymphoma (DLBCL). This meta-analysis aimed to evaluate the prognostic value of sarcopenia in patients with DLBCL.MethodsPubMed, Embase, and Cochrane Library databases were searched to identify trials exploring the association between sarcopenia and prognosis in patients with DLBCL treated with chemotherapy. A meta-analysis of overall survival (OS), progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…The present study showed that the incidence of sarcopenia was 29.1% at baseline and 36.9% at the end-of-treatment, which is in accordance with prior studies reporting a sarcopenia incidence of 23.9%–55.6% in DLBCL patients [ 18 ]. Although there was no significant difference in BMI before and after treatment, SMI was found to significantly decrease at end-of-treatment compared with baseline.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The present study showed that the incidence of sarcopenia was 29.1% at baseline and 36.9% at the end-of-treatment, which is in accordance with prior studies reporting a sarcopenia incidence of 23.9%–55.6% in DLBCL patients [ 18 ]. Although there was no significant difference in BMI before and after treatment, SMI was found to significantly decrease at end-of-treatment compared with baseline.…”
Section: Discussionsupporting
confidence: 93%
“…It is defined as a gradual decrease in both the mass and/or strength of the skeletal muscle. At present, the diagnosis of sarcopenia mainly relies on the measurement of SMA at the L3 level using a single-slice CT image which needs to be subsequently normalized as SMI [ 18 ]. The whole-body PET/CT scan is a routine examination for diagnosing, staging, and evaluating treatment response in malignancies, including DLBCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sarcopenia, defined by the depletion of skeletal muscle, has been recognized as an unfavorable prognostic factor and predictor of chemotherapy toxicity in older patients with solid tumors [27][28][29][30]. In patients with DLBCL, several studies showed that sarcopenic patients had poor outcomes in terms of survival and progression-free survival (PFS) [31][32][33][34][35] as well as treatment-related mortality and treatment discontinuation [33,36,37]. However, other studies did not retain sarcopenia as an independent prognostic factor [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a R-IPI poor risk score and a higher NLR, the R-COP regimen, and infections were predictors of shorter PFS and OS. Upon reviewing the literature, conflicting results were found, and the predictive value of sarcopenia in patients with poor survival was not confirmed for hematological malignancies (11,(36)(37)(38)(39)(40). This difference could be directly associated with the heterogeneity of samples studied, such as lymphoma variants, type of treatment, stage, SMI thresholds, and imaging tools.…”
Section: Discussionmentioning
confidence: 99%